Supercentenarians
XV, 323 p. 52 illus.
Keywords: Does human mortality after age 110 continue to rise, level off, or start to decline? This book describes a concerted, international research effort undertaken with the goal of establishing a database that allows the best possible description of the mortality trajectory beyond the age of 110. The International Database on Longevity (IDL) is the result of this ongoing effort. The IDL contains exhaustive information on validated cases of supercentenarians (people 110 years and older) and allows unbiased estimates of mortality after age 110. The main finding is remarkable: human mortality after age 110 is flat at a probability of death of 50% per year. The sixteen chapters of this book discuss age validation of exceptional longevity, data on supercentenarians in a series of countries, structure and contents of the IDL, and statistical analysis of human mortality after age 110. Several chapters include short accounts of specific supercentenarians that add life to demographic research.